العقيدة العسكرية الجزائرية الأفاق والتطورات - - يوسف زغدان (جامعة المسيلة, 2022)
من خلال هذه الدراسة الموسومة بالعقيدة العسكرية الجزائرية الآفاق والتطورات، ركزنا على التصور الجزائري للعقيدة العسكرية وإلى أهم محدداتها. فالموقع الجيوستراتيجي للجزائر باعتبارها نقطة تقاطع بين إفريقيا وأوروبا فرض عليها عدة تحديات، كما أن البيئة الإقليمية المحيطة بالجزائر تشهد اضطرابات كبيرة على المستوى الأمني، وهذا ما ألقى بظلاله على أمن الجزائر. فالأزمة الليبية والأزمة في مالي بالإضافة إلى التدخل الفرنسي في هذا الأخير والتوتر مع الجارة المغرب وقضية النزاع في الصحراء الغربية، بالإضافة إلى الضغوطات الدولية المتزايدة أدى بالجزائر إلى إعادة مراجعة لعقيدتها العسكرية، حيث في التعديل الدستوري 2021 أدرج مادة تسمح للجيش بالمشاركة في مهمات خارج الحدود لحماية مصالح الجزائر وهذا يعتبر تغييرا جوهريا في العقيدة العسكرية التي كانت من ثوابتها ومرتكزاتها عدم التدخل في الشؤون الداخلية للدول. Summary : Through this study, which is tagged with the Algerian military doctrine, prospects and developments, we focused on the Algerian conception of the military doctrine and its most important determinants. Algeria's geostrategic position as a point of intersection between Africa and Europe has imposed several challenges on it, and the regional environment surrounding Algeria is witnessing great turmoil at the security level, and this has cast a shadow over Algeria's security. The Libyan crisis and the crisis in Mali, in addition to the French intervention in the latter, tension with neighboring Morocco and the issue of the conflict in Western Sahara, in addition to the increasing international pressures led Algeria to re-review its military doctrine, as in the 2021 constitutional amendment an article was included that allows the army to participate in missions outside the borders to protect Algeria's interests, and this is considered a fundamental change in the military doctrine, which was one of its constants and foundations of non-interference in the internal affairs of countries.
Keywords: العقيدة -العسكر- الجزائر الأفاق-التطورات